2012
DOI: 10.1016/j.gene.2012.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Role of the RAD51 G172T polymorphism in the clinical outcome of cervical cancer patients under concomitant chemoradiotherapy

Abstract: Introduction: Cervical cancer is one of the most common cancers diagnosed in women worldwide. Mammalian cells are constantly exposed to a wide variety of genotoxic agents from both endogenous and exogenous sources. The RAD51 protein is required for meiotic and mitotic recombination and plays a central role in homology-dependent recombinational repair of double-strand breaks (DSBs). Given the functional relevance of the DNA repair system on carcinogenesis, potential associations between genetic polymorphisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Previous studies have shown that therapy response can vary significantly among patients due to interindividual variations of DNA repair activity caused by the presence of genetic alterations in DNA repair genes which results in DNA repair deficiency and hence with chemoradiotherapy sensitization (Nogueira et al, 2012, de las Penas et al, 2006, Shi et al, 2012, Chung et al, 2006. Because of the importance of this process in determining sensitivity and resistance, components of the DNA damage repair pathways have been studied with regard to genetic variation and response to therapy (Hildebrandt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that therapy response can vary significantly among patients due to interindividual variations of DNA repair activity caused by the presence of genetic alterations in DNA repair genes which results in DNA repair deficiency and hence with chemoradiotherapy sensitization (Nogueira et al, 2012, de las Penas et al, 2006, Shi et al, 2012, Chung et al, 2006. Because of the importance of this process in determining sensitivity and resistance, components of the DNA damage repair pathways have been studied with regard to genetic variation and response to therapy (Hildebrandt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The mutation of this gene may reverse the risk of cancers. Many documents have reported the association of RAD51 genetic factors with human cancers (Poplawski et al, 2006;Lu et al, 2007;Gresner et al, 2012;Nogueira et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is located on the human chromosome 15q15.1, which contains 10 exons and encodes a protein with 339 amino acids (Lu et al, 2007;Nogueira et al, 2012). RAD51 is highly polymorphic: It has more than 100 SNPs, some of which have been suggested to contribute to cancers the risk of variable (Poplawski et al, 2006;Lu et al, 2007;Nogueira et al, 2012;Gresner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphisms in genes involved in DNA repair could result in variations in efficacy and accuracy of DNA repair enzymes and consequently significantly affect the toxicity, effectiveness and therapy outcome. By their role in therapy response, genetic polymorphisms in these genes can influence the patient's survival and be useful as prognostic and predictive markers in cancer [40][41][42][43] . Moreover, with the development of DDR protein inhibitors for cancer treatment, research on targeting molecular pathways, such as DNA repair, is becoming one of the most important areas in clinical oncology [43][44][45][46][47][48] .…”
Section: Oc and Dna Repairmentioning
confidence: 99%